História natural de Bothrops leucurus Wagler, 1824 (Serpentes, Viperidae) da Mata Atlântica da Paraíba, Brasil - Oliveira, Pâmella Albinati (2013)
The family Viperidae is composed of snakes with solenoglyph dentition, which are highly specialized for venom inoculation. In Brazil there are 32 representatives of this family, including the Bothrops genus that best represents the Viperidae and it is subdivided into groups that share ecological and morphological similarities: B. alternatus, B. atrox, B. neuwiedi, B. jararaca, B. jararacussu and B. taeniatus. They are viviparous snakes with a mating period between the months of March and July and, after fertilization, which occurs in spring, their parturition happens between January and May. Bothrops leucurus belongs to the B. atrox group and presents ecological aspects similar to the most related species of the genus (i.e. B. atrox and B. moojeni). Bothrops leucurus is a primarily nocturnal snake, distributed mainly in the Northeastern Atlantic Forest. Young individuals are mostly found near riverbanks and adults on the litter, mainly due to the availability of food in these places. The mating period occurs in March, having, therefore, seasonal reproduction, with retention of sperm in a twist located in the female's posterior uterus, until the eggs are properly prepared for fertilization to occur in October, leading to parturition and the recruitment period in February and March. Bothrops leucurus has a generalist diet and ontogeny in the diet, with young individuals feeding preferentially on ectothermic prey and adults on endothermic prey. The study of snakes of medical interest can contribute to the mitigation of snakebites. Furthermore, from an ecological perspective, understanding the ecology of a species, we are able to contribute to its conservation and the environment that it inhabits. Thus, the present work aims to contribute with information on the diet, use of micro-habitat and reproductive biology of Bothrops leucurus mainly from the state of Paraíba.